2017
DOI: 10.1007/s13204-017-0551-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled nanotubes from single fluorescent amino acid

Abstract: Self-assembly of biomolecules has gained increasing attention as it generates various supramolecular structural assemblies having potential applications principally in biomedical sciences. Here, we show that amino acid like tryptophan or tyrosine readily aggregates as nanotubes via a simple self-assembly process. These were characterized by FTIR, scanning electron microscopy, and by fluorescence microscopy. Nanotubes prepared from tryptophan are having *200 nm inner diameter and those from tyrosine are having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 43 publications
3
68
0
Order By: Relevance
“…It has also been reported that by changing the amount of water volume, there would be a change in the shape of the final product from nanotube to nanowire [36,42] . Generally, in the present study, the presence of hydrogen bonding and π ‐ π stacking interactions for minimizing the surface energy lead to the formation of the phenylalanine amino acids tubes [20] . Therefore, the medium concentration (0.5 mg/ml) is the optimal concentration of phenylalanine solution for the synthesis of nanotubes as an ideal drug nanocarrier.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…It has also been reported that by changing the amount of water volume, there would be a change in the shape of the final product from nanotube to nanowire [36,42] . Generally, in the present study, the presence of hydrogen bonding and π ‐ π stacking interactions for minimizing the surface energy lead to the formation of the phenylalanine amino acids tubes [20] . Therefore, the medium concentration (0.5 mg/ml) is the optimal concentration of phenylalanine solution for the synthesis of nanotubes as an ideal drug nanocarrier.…”
Section: Resultssupporting
confidence: 53%
“…As a result, in the ring deformation region of around 840–500 cm −1 , some certain changes are taken place which further suggest the interactions of π ‐ π and C−H− π . Moreover, OH and CH stretching vibrations indicate their peaks at 3226 cm −1 and 3839 cm −1 and at 2670 cm −1 , respectively [20,49] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] These nanotubes exhibited fluorescence when excited at 385 (blue), 488 (yellow) and 561 (red) nm.…”
Section: Amino Acid Based Nanostructuresmentioning
confidence: 99%
“…[14c] (I) FESEM images of Trp nanotubes (scale bar 200 nm). [35] Figures reproduced with permission from respective references.…”
Section: Figurementioning
confidence: 99%